Analysis of the Effect of Inlet Compressor Temperature on the Thermal Efficiency of PLTG Unit 3.2 in Grati - Purwanto, Didik (Department of Mechanical and Industrial Engineering, 2024)
PLTGU Grati block 3 has two gas turbines, namely unit 3.1 and unit 3.2, with a Net Capacity of 145 MW for each gas turbine. In PLTG unit 3.2 Grati, there is an issue related to differences in thermal efficiency values caused by changes in the inlet compressor temperature. The thermal efficiency value of PLTG unit 3.2 Grati is high when the compressor's inlet temperature is low. Therefore, to determine the effect of the compressor's inlet temperature on the thermal efficiency value of PLTG unit 3.2, a calculation process of parameters affecting thermal efficiency values is conducted for analysis purposes. In this research, calculations were performed for three compressor inlet temperature data points, namely at temperatures of 296.69 K, 299.49 K, and 304.11 K, resulting in gas turbine thermal efficiency values of 32.17%, 31.84%, and 31.79%, respectively. Based on the calculation results, it is shown that as the compressor's inlet temperature increases, the thermal efficiency value decreases.